2022
DOI: 10.1021/acs.est.2c04348
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Sunlight, Titanium Dioxide, and Microbes Enhances Cellulose Diacetate Degradation in the Ocean

Abstract: Sunlight chemically transforms marine plastics into a suite of products, with formulation—the specific mixture of polymers and additives—driving rates and products. However, the effect of light-driven transformations on subsequent microbial lability is poorly understood. Here, we examined the interplay between photochemical and biological degradation of fabrics made from cellulose diacetate (CDA), a biobased polymer used commonly in consumer products. We also examined the influence of ∼1% titanium dioxide (TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…While our additive-free PE photoproducts (AFP) differentially regulated thousands of genes, the PE plastic bags (CBP, RBP) contained inorganic additives and their photoproducts differentially regulated few to none. Inorganic additives are well understood to facilitate polymer degradation, ,, and our results suggest that inorganic additives may also attenuate toxicity by altering the chemical composition of photoproducts. However, inorganic additives, including TiO 2 , carry notable environmental risks. Determining the net balance of the risks and benefits of photocatalytic additives in plastics is thus critical to identify next-generation, functional materials with low environmental persistence and breakdown products that pose minimal harm to human and ecosystem health.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…While our additive-free PE photoproducts (AFP) differentially regulated thousands of genes, the PE plastic bags (CBP, RBP) contained inorganic additives and their photoproducts differentially regulated few to none. Inorganic additives are well understood to facilitate polymer degradation, ,, and our results suggest that inorganic additives may also attenuate toxicity by altering the chemical composition of photoproducts. However, inorganic additives, including TiO 2 , carry notable environmental risks. Determining the net balance of the risks and benefits of photocatalytic additives in plastics is thus critical to identify next-generation, functional materials with low environmental persistence and breakdown products that pose minimal harm to human and ecosystem health.…”
Section: Resultsmentioning
confidence: 69%
“…23,25,28 Several studies have recently demonstrated that the formulation of plastics (i.e., the combination of polymer and additives) substantially influences the rates and chemical composition of resultant photoproducts. 12,13,15,17,36 For example, titanium dioxide (TiO 2 ) inorganic additives, used as white pigments in singleuse PE bags, promoted photochemical degradation and resulted in unique photoproduct compositions, forming a complex mixture of tens of thousands of compounds. 13 ces by changing the photoproduct composition of plastics warrants study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a matter of fact, there are several mechanisms underlying seawater plastic degradation (photooxidation, biodegradation by microorganisms, chemical–mechanical degradation, hydrolysis, etc. [ 32 , 33 , 34 ]), and only some of these can be simulated in a laboratory setting. Furthermore, while the IRMS measurements performed in this study and by other researchers [ 27 ] provide a background for highlighting a degradation process, no exact degradation pathway involved in shifting isotopic values can in effect be differentiated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, DOSY has recently been applied to determine the MW of natural polymers such as lignin and heparin, relating 1 H and DOSY spectra to GPC-determined MWs using multivariate correlations. , DOSY should therefore be a suitable alternative method to GPC for the analysis of plastic consumer products, which span a wide range of polymer types and presumably MWs. Furthermore, the potential for DOSY as a method to determine polymer MWs for experimental work (e.g., degradation of polymers in engineered or environmental systems) has only recently been introduced and not yet fully validated. To verify the applicability of this analytical approach requires an investigation of the methodological considerations that control accuracy and precision of MW assessments via DOSY.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the average values and dispersity of MWs have large influences on the physical properties of synthetic polymer resins. , A single homopolymer (meaning, of one chemical structure) may be synthesized with different MWs, which are then used for different applications based on the resulting thermal or mechanical properties. When leaked into the environment, only low MW constituents of polymers (even water-soluble ones) are available for biodegradation, and MW is expected to decrease upon exposure to sunlight via chain scission reactions. Therefore, polymer MW is expected to be a controlling factor for their environmental fate. These collective roles that MW plays call for analytical approaches for polymer MW that are efficient, accurate, and precise.…”
Section: Introductionmentioning
confidence: 99%